Expanding Access: Cost-effectiveness of Cochlear Implantation and Deaf Education in Asia. (October 2019) - Emmett, Susan D.; Sudoko, Chad K.; Tucci, Debara L.; Gong, Wenfeng; Saunders, James E.; ,; Akhtar, Nasima; Bhutta, Mahmood F.; Touch, Sokdavy; Pradhananga, Rabindra Bhakta; Mukhtar, Nadeem; Martinez, Norberto; et al.
Objective: To determine the cost-effectiveness of cochlear implantation (CI) with mainstream education and deaf education with sign language for treatment of children with profound sensorineural hearing loss in low- and lower-middle income countries in Asia. Study Design: Cost-effectiveness analysis. Setting: Bangladesh, Cambodia, India, Indonesia, Nepal, Pakistan, Philippines, and Sri Lanka participated in the study. Subjects and Methods: Costs were obtained from experts in each country with known costs and published data, with estimation when necessary. A disability-adjusted life-years model was applied with 3% discounting and 10-year length of analysis. A sensitivity analysis was performed to evaluate the effect of device cost, professional salaries, annual number of implants, and probability of device failure. Cost-effectiveness was determined with the World Health Organization standard of cost-effectiveness ratio per gross domestic product (CER/GDP) per capita <3. Results: Deaf education was cost-effective in all countries except Nepal (CER/GDP, 3.59). CI was cost-effective in all countries except Nepal (CER/GDP, 6.38) and Pakistan (CER/GDP, 3.14)—the latter of which reached borderline cost-effectiveness in the sensitivity analysis (minimum, maximum: 2.94, 3.39). Conclusion: Deaf education and CI are largely cost-effective in participating Asian countries. Variation in CI maintenance and education-related costs may contribute to the range of cost-effectiveness ratios observed in this study.